Management of Improving the Quality of Islamic Boarding School Education in the Era of Society 5.0 in Facing Global Competition - Ningsih, Sri Rahayu; Patimah, Siti; Murtafiah, Nurul Hidayati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to: (1) describe the general educational management of Pondok Pesantren Hidayatul Mubtadi'in, Al Ishlah, and Al Huda in Lampung Province; (2) analyze the quality improvement management applied by these Islamic boarding schools in responding to the demands of the Society 5.0 era; and (3) formulate a quality management model that aligns with contemporary needs while maintaining the pesantren's salafiyah identity. This study is qualitative research with a multisite design. Data were obtained through participatory observation, semi-structured interviews, and document analysis, supported by relevant literature. Data were analyzed using Miles' interactive model involving data reduction, data display, and conclusion drawing, combined with triangulation to ensure data validity. The findings show that the three Islamic boarding schools still apply traditional management patterns centered on kyai authority, classical learning methods, and evaluation systems emphasizing mastery of religious texts and character formation. However, initiatives to improve educational quality have begun to appear, including the integration of religious and general curriculum, strengthening of human resources, and gradual improvement of facilities while upholding principles of halal practice and institutional independence. These findings indicate that Islamic boarding school modernization can be carried out without abandoning tradition, through innovations that remain adaptive and culturally rooted. The resulting quality management model integrates Islamic values, traditional Islamic boarding school approaches, and relevant 21st-century principles, offering a framework for Islamic boarding schools to enhance educational quality while preserving their core identity.